Doped Titanium Dioxide Films Prepared by Pulsed Laser Deposition Method - Juguang Hu; Huabin Tang; Xiaodong Lin; Zhongkuan Luo; Huiqun Cao; Qiwen Li; Yi Liu; Jinghua Long; Pei Wang (International Journal of Photoenergy)
TiO2 was intensively researched especially for photocatalystic applications. The nitrogen-doped TiO2 films prepared by pulsed laser deposition (PLD) method were reviewed, and some recent new experimental results were also presented in this paper. A new optical transmission method for evaluating the photocatalystic activity was presented. The main results are (1) PLD method is versatile for preparing oxide material or complex component films with excellent controllability and high reproducibility. (2) Anatase nitrogen-doped TiO2 films were prepared at room temperature, 200°C, and 400°C by PLD method using novel ceramic target of mixture of TiN and TiO2. UV/Vis spectra, AFM, Raman spectra, and photocatalystic activity for decomposition of methyl orange (MO) tests showed that visible light response was improved at higher temperature. (3) The automatic, continuous optical transmission autorecorder method is suitable for detecting the photodecomposition dynamic process of organic compound.